Perception, understanding, and action: attitudes of climate change in the Hungarian population - Jankó, Ferenc; Bertalan, Laura; Hoschek, Mónika; Komornoki, Karolina; Németh, Nikoletta; Papp-VancsóJudit (Hungarian Geographical Bulletin, 2018)
This study is based on a non-representative, national level survey sample whose main purpose is to interpret the general population’s understanding of climate change. The study also provides an examination of correlations between climate change concerns and the taking of individual action as well as the relationship between pro-environmental thinking and climate change scepticism. Our results show a moderate correlation between the general population’s concerns and the professional views on the subject, known in the literature as the New Environmental Paradigm scale and Scepticism scale, but a significantly weaker correlation when it comes to taking action against climate change. Factors relating to the respondents, such as residence settlement type, education level, gender, age, personal and social values, or casual attributions in relation to climate change heavily influence this weaker correlation. Most respondents assessed climate change as a current (urgent), but geographically remote phenomenon. This is a clear indication of problems associated with cognitive conceptualization and the localization of climate change in communication. The target audience must be taken into account when designing climate change communications because interpretations of climate change can vary widely and cover a broad range attitudes ranging from concern about to issue all the way to climate change scepticism. This also applies to views concerning responsibility for climate change with some believing it is a political responsibility and others believing it is a scientific responsibility.